Mathematical and statistical analysis of disease COVID-19 and implications for future projections (Research, Society and Development, 2020)
The mathematical and statistical analysis of the disease COVID 19 and implications for future projections, shows a survey using the data collected from the cases of the new coronavirus, related to the number of cases and deaths resulting from the disease. The methodology used was of the quantitative type, supported by data made available by the Brazilian Institute of Geography and Statistics and by the Ministry of Health, where mathematical models were generated, polynomials of the 3rd and 4th grade, referring to the numbers of deaths and cases respectively. The objective is to unveil the main circumstances that contribute to the increase in the lethality rate of the disease, in addition to showing what happened for every 10,000 cases and deaths from the disease. The estimated results, are correlated with the demographic density, indicated in which locations there is a greater advance of the pandemic, in addition to sampling estimated time projections of the extinction of the advance in the number of cases and possible deaths, considering the restriction measures adopted considering the possibilities the emergence of a new curve, corroborating so that the competent authorities can devise strategies to contain it.